Zeolite membrane composite and method for producing the same

JP7629676B2Active Publication Date: 2025-02-14NGK CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022580618
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-10
Filing Date
2022-02-07
Publication Date
2025-02-14
Estimated Expiration
2042-02-07

Smart Images

  • Figure 0007629676000003
    Figure 0007629676000003
  • Figure 0007629676000004
    Figure 0007629676000004
  • Figure 0007629676000005
    Figure 0007629676000005
Patent Text Reader

Abstract

This zeolite membrane composite (1) is provided with a porous support (11) and a zeolite membrane (12) which is provided on the support (11) and comprises RHO-type zeolite. When the surface of the zeolite membrane (12) is measured by an X-ray diffraction method, the peak intensity originating from the (310) plane of the RHO-type zeolite is at most 0.4 times the peak intensity originating from the (110) plane, and the peak intensity originating from the (211) plane is at most 0.3 times the peak intensity originating from the (110) plane. As a result, it is possible to easily provide a zeolite membrane composite (1) with excellent separation performance and permeability.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a zeolite membrane composite and a method for producing a zeolite membrane composite. [Reference to Related Applications] This application claims the benefit of priority from Japanese patent application JP2021-19722, filed on February 10, 2021, the entire disclosure of which is incorporated herein by reference. [Background technology]

[0002] JP 2018-130719 A (Reference 1) discloses an RHO-type zeolite membrane formed on a porous support using an organic structure-directing agent. In an X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity around 2θ=18.7° is 1.0 times or more the peak intensity around 2θ=8.3°, and the peak intensity around 2θ=14.4° is 0.5 times or more the peak intensity around 2θ=8.3°. Therefore, in the zeolite membrane of Reference 1, the zeolite crystals grow in an oriented manner so that the (310) and (211) planes are nearly parallel to the membrane surface. In addition, in "Preparation of Rho Zeolite Membranes on Tubular Supports" (MEMBRANE, 2016, Vol. 41, No. 2, pp. 81-86) (Reference 2) by Bo Liu and four others, a method for forming an RHO-type zeolite membrane on a porous support without using an organic structure-directing agent is disclosed.

[0003] Incidentally, a dense zeolite membrane is necessary to obtain a zeolite membrane composite with high separation performance. However, for example, the raw material solution used to form an aluminosilicate type RHO zeolite membrane has low fluidity, so gaps are likely to occur at the grain boundaries, making it difficult to form a dense thin film. In Literature 1, the denseness of the zeolite membrane is improved by repeating hydrothermal synthesis multiple times, but this increases the manufacturing cost of the zeolite membrane composite. In Literature 2, a dense membrane is obtained by performing hydrothermal synthesis for six days, but this also increases the manufacturing cost of the zeolite membrane composite. Also, in Literature 2, the thickness of the zeolite membrane is about 2 μm, but the water permeation amount (water flux) is 1 kg / m 2 h or less, the values ​​are low. Zeolite membrane composites are required to have not only high separation performance but also high permeation capacity. Summary of the Invention

[0004] The present invention is directed to a zeolite membrane composite, and has an object to easily provide a zeolite membrane composite which has a zeolite membrane made of RHO type zeolite and has high separation performance and permeation amount.

[0005] A zeolite membrane composite according to a preferred embodiment of the present invention comprises a porous support and a zeolite membrane formed on the support and made of RHO-type zeolite. When the surface of the zeolite membrane is measured by an X-ray diffraction method, the peak intensity derived from the (310) plane of the RHO-type zeolite is 0.4 times or less the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane is 0.3 times or less the peak intensity derived from the (110) plane. The zeolite membrane has a silicon / aluminum molar ratio of 1.2 to 3.0. do.

[0006] According to the present invention, it is possible to easily provide a zeolite membrane composite which has a zeolite membrane made of RHO type zeolite and has high separation performance and high permeation amount.

[0007] Preferably, the support is provided with a composite layer in which a part of the zeolite membrane is embedded in pores, and the thickness of the composite layer is smaller than the thickness of the zeolite membrane on the support.

[0008] Preferably, the zeolite membrane has a thickness of 5 μm or less, and the composite layer has a thickness of 1 μm or less.

[0010] The present invention is also directed to a method for producing a zeolite membrane composite.

[0011] A method for producing a zeolite membrane composite according to a preferred embodiment of the present invention comprises the steps of: a) attaching seed crystals of RHO zeolite onto a porous support; and b) immersing the support in a raw material solution and growing RHO zeolite from the seed crystals by hydrothermal synthesis to form a zeolite membrane on the support. In the raw material solution, the molar ratio of silicon / aluminum is 2 to 20, the molar ratio of sodium / aluminum is 10 to 100, the molar ratio of cesium / aluminum is 0.5 to 10, and the molar ratio of water / aluminum is 500 to 5000. H 2 O / SiO 2 The molar ratio of do.

[0012] Preferably, the viscosity of the raw material solution at 20° C. is 1 to 150 mPa·s.

[0013] The above and other objects, features, aspects and advantages will become apparent from the following detailed description of the invention which proceeds with reference to the accompanying drawings. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a cross-sectional view of a zeolite membrane composite. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing a part of the zeolite membrane composite. [Diagram 3] FIG. 2 shows an X-ray diffraction pattern obtained from the surface of a zeolite membrane. [Figure 4]FIG. 2 is a diagram showing a schematic diagram of the crystal structure of a zeolite membrane. [Diagram 5] FIG. 2 is a diagram showing a flow of production of a zeolite membrane composite. [Figure 6] FIG. [Figure 7] FIG. 1 is a diagram showing the flow of separation of a mixed material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] FIG. 1 is a cross-sectional view of a zeolite membrane composite 1. FIG. 2 is a cross-sectional view showing an enlarged portion of the zeolite membrane composite 1. The zeolite membrane composite 1 includes a porous support 11 and a zeolite membrane 12 provided on the support 11. The zeolite membrane is at least a membrane of zeolite formed on the surface of the support 11, and does not include a membrane in which zeolite particles are simply dispersed in an organic membrane. In FIG. 1, the zeolite membrane 12 is drawn with a thick line. In FIG. 2, the zeolite membrane 12 and a composite layer 13, which will be described later, are drawn with parallel oblique lines. In FIG. 2, the zeolite membrane 12 and the composite layer 13 are drawn thicker than they actually are.

[0016] The support 11 is a porous member that is permeable to gas and liquid. In the example shown in FIG. 1, the support 11 is a monolithic support having a single continuous columnar body formed integrally and provided with a plurality of through holes 111 each extending in the longitudinal direction (i.e., the left-right direction in FIG. 1). In the example shown in FIG. 1, the support 11 is substantially cylindrical. The cross section perpendicular to the longitudinal direction of each through hole 111 (i.e., cell) is, for example, substantially circular. In FIG. 1, the diameter of the through hole 111 is drawn larger than the actual diameter, and the number of the through holes 111 is drawn smaller than the actual number. The zeolite membrane 12 is formed on the inner circumferential surface of the through hole 111, and covers the inner circumferential surface of the through hole 111 over substantially the entire surface.

[0017] The length of the support 11 (i.e., the length in the left-right direction in FIG. 1) is, for example, 10 cm to 200 cm. The outer diameter of the support 11 is, for example, 0.5 cm to 30 cm. The distance between the central axes of adjacent through holes 111 is, for example, 0.3 mm to 10 mm. The surface roughness (Ra) of the support 11 is, for example, 0.1 μm to 5.0 μm, and preferably 0.2 μm to 2.0 μm. The shape of the support 11 may be, for example, a honeycomb shape, a flat plate shape, a tubular shape, a cylindrical shape, a columnar shape, or a polygonal column shape. When the shape of the support 11 is a tubular or cylindrical shape, the thickness of the support 11 is, for example, 0.1 mm to 10 mm.

[0018] The material of the support 11 may be any of various substances (e.g., ceramics or metals) as long as it has chemical stability in the process of forming the zeolite membrane 12 on the surface. In this embodiment, the support 11 is formed of a ceramic sintered body. Examples of ceramic sintered bodies selected as the material of the support 11 include alumina, silica, mullite, zirconia, titania, yttria, silicon nitride, and silicon carbide. In this embodiment, the support 11 contains at least one of alumina, silica, and mullite.

[0019] The support 11 may contain an inorganic binder, which may be at least one of titania, mullite, sinterable alumina, silica, glass frit, clay minerals, and sinterable cordierite.

[0020] The average pore diameter of the support 11 is, for example, 0.01 μm to 70 μm, and preferably 0.05 μm to 25 μm. The average pore diameter of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed is 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. The average pore diameter can be measured, for example, by a mercury porosimeter, a perm porosimeter, or a nanoperm porosimeter. Regarding the distribution of pore diameters throughout the support 11, including the surface and the inside, D5 is, for example, 0.01 μm to 50 μm, D50 is, for example, 0.05 μm to 70 μm, and D95 ​​is, for example, 0.1 μm to 2000 μm. The porosity of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed is, for example, 20% to 60%.

[0021] The support 11 has a multilayer structure in which, for example, a plurality of layers having different average pore diameters are laminated in the thickness direction. The average pore diameter and sintered grain size in the surface layer including the surface on which the zeolite membrane 12 is formed are smaller than the average pore diameter and sintered grain size in the layers other than the surface layer. The average pore diameter of the surface layer of the support 11 is, for example, 0.01 μm to 1 μm, and preferably 0.05 μm to 0.5 μm. When the support 11 has a multilayer structure, the materials for each layer can be those described above. The materials for the layers forming the multilayer structure may be the same or different.

[0022] The zeolite membrane 12 is a porous membrane having fine pores (micropores). The zeolite membrane 12 can be used as a separation membrane that separates a specific substance from a mixture of a plurality of types of substances by utilizing a molecular sieve effect. Other substances are less likely to permeate the zeolite membrane 12 than the specific substance. In other words, the amount of the other substances that permeates the zeolite membrane 12 is smaller than the amount of the specific substance that permeates the zeolite membrane 12. The surface roughness (Ra) of the zeolite membrane 12 is, for example, 5 μm or less, preferably 2 μm or less, more preferably 1 μm or less, and even more preferably 0.5 μm or less.

[0023] The zeolite membrane 12 is composed of zeolite with an RHO structure. In other words, the zeolite membrane 12 is made of zeolite with the structure code "RHO" defined by the International Zeolite Society. The XRD pattern obtained from the surface of the zeolite membrane 12, shown in FIG. 3 described later, has peak positions that match those of the XRD pattern expected from the structure of RHO zeolite. The zeolite membrane 12 is typically composed only of RHO zeolite, but depending on the production method, the zeolite membrane 12 may contain a small amount (for example, 1 mass % or less) of a substance other than RHO zeolite.

[0024] The maximum number of rings in RHO zeolite is 8, and the average pore diameter is defined as the arithmetic mean of the short diameter and long diameter of the 8-ring pores. The 8-ring pores are micropores in which the number of oxygen atoms in the portion in which the oxygen atoms are bonded to the T atoms described below to form a ring structure is 8. The intrinsic pore diameter of RHO zeolite is 0.36 nm × 0.36 nm, and the average pore diameter is 0.36 nm. The average pore diameter of the zeolite membrane 12 is smaller than the average pore diameter of the support 11 in the vicinity of the surface on which the zeolite membrane 12 is formed.

[0025] An example of the RHO-type zeolite constituting the zeolite membrane 12 is an aluminosilicate zeolite in which the atom (T atom) located at the center of the oxygen tetrahedron (TO4) constituting the zeolite is composed of silicon (Si) and aluminum (Al). A part of the T atoms may be substituted with other elements (gallium, titanium, vanadium, iron, zinc, tin, etc.). This makes it possible to change the pore size and adsorption characteristics. The molar ratio of silicon / aluminum in the zeolite membrane 12 (a value obtained by dividing the number of moles of silicon atoms by the number of moles of aluminum atoms; the same applies below) is preferably 1 to 10, more preferably 1.1 to 5, and further preferably 1.2 to 3. This makes it possible to improve the hydrophilicity of the zeolite membrane 12. The molar ratio of silicon / aluminum can be measured by EDS (energy dispersive X-ray spectroscopy) analysis. The silicon / aluminum ratio in the zeolite membrane 12 can be adjusted by adjusting the blending ratio in the raw material solution described later (the same applies to the ratios of other elements). Of course, the RHO type zeolite is not limited to the aluminosilicate type.

[0026] Typically, the zeolite membrane 12 contains sodium (Na). The molar ratio of sodium / aluminum in the zeolite membrane 12 is preferably 10 to 100, and more preferably 20 to 90. This stabilizes the structure of the RHO-type zeolite (such as suppressing crystal collapse). The zeolite membrane 12 preferably further contains cesium (Cs). The molar ratio of cesium / aluminum in the zeolite membrane 12 is preferably 0.5 to 3.0, and more preferably 1.0 to 2.0. The zeolite membrane 12 may contain other alkali metals such as potassium (K) and rubidium (Rb). In addition, some or all of the cations are converted to protons (H + ) and ammonium ion (NH4 + ) and the like.

[0027] One example of the zeolite membrane 12 is manufactured without using an organic substance called a structure-directing agent (hereinafter also referred to as "SDA"). In this case, the zeolite membrane 12 does not contain SDA. In the zeolite membrane 12 that does not contain SDA, the pores are appropriately secured. The zeolite membrane 12 may be manufactured using SDA. In this case, it is preferable that the SDA is almost or completely removed after the formation of the zeolite membrane 12. For example, 18-crown-6-ether or the like can be used as the SDA.

[0028] 3 is a diagram showing an example of an X-ray diffraction (XRD) pattern obtained by irradiating the surface of the zeolite membrane 12 with X-rays. In obtaining the XRD pattern, for example, CuKα radiation is used as a radiation source of an X-ray diffractometer, but other types of radiation sources may be used. As described above, the peak positions of the XRD pattern obtained from the zeolite membrane 12 coincide with those of the XRD pattern expected from the structure of RHO-type zeolite.

[0029] In the zeolite membrane 12, the peak intensity in the XRD pattern around 2θ=18.7° is 0.4 times or less than the peak intensity in the vicinity of 2θ=8.3°, and the peak intensity in the vicinity of 2θ=14.4° is 0.3 times or less than the peak intensity in the vicinity of 2θ=8.3°. The peak in the vicinity of 2θ=18.7° is a peak existing in the range of 2θ=18.7°±0.9° and originates from the (310) plane of RHO-type zeolite. The peak in the vicinity of 2θ=8.3° is a peak existing in the range of 2θ=8.3°±0.6° and originates from the (110) plane. The peak in the vicinity of 2θ=14.4° is a peak existing in the range of 2θ=14.4°±0.8° and originates from the (211) plane. Therefore, in the zeolite membrane 12, the peak intensity derived from the (310) plane of the RHO zeolite is 0.4 times or less than the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane is 0.3 times or less than the peak intensity derived from the (110) plane. Thus, the zeolite membrane 12 is an oriented membrane with a relatively high peak intensity derived from the (110) plane.

[0030] The ratio of the peak intensity derived from the (310) plane divided by the peak intensity derived from the (110) plane is more preferably 0.3 or less. The lower limit of this ratio is not particularly limited, but is, for example, 0.05. The ratio of the peak intensity derived from the (211) plane divided by the peak intensity derived from the (110) plane is more preferably 0.2 or less. The lower limit of this ratio is not particularly limited, but is, for example, 0.05. The peak intensity is the height of the bottom line in the XRD pattern, that is, the height excluding background noise components. The bottom line in the XRD pattern is obtained, for example, by the Sonneveld-Visser method or the spline interpolation method.

[0031] FIG. 4 is a diagram showing a schematic crystal structure of the zeolite membrane 12. In FIG. 4, the composite layer 13 described later is omitted. In the RHO-type zeolite, continuous pores are formed in which 8-membered ring pores are connected to each other. In the zeolite membrane 12 having a relatively high peak intensity derived from the (110) plane, the (110) plane is oriented nearly parallel to the surface of the zeolite membrane 12, and many openings 121 of the continuous pores are located on the surface. As a result, in the separation of a mixed substance described later, the access of a substance having high permeability to the zeolite membrane 12 (hereinafter referred to as a "highly permeable substance") to the continuous pores increases, so that the permeation amount (permeation rate) of the highly permeable substance in the zeolite membrane 12 increases and the separation performance also increases.

[0032] In the zeolite membrane composite 1 of FIG. 2, during the formation of the zeolite membrane 12, RHO zeolite is also generated in the pores of the support 11. In other words, the support 11 is provided with a layer 13 (hereinafter referred to as "composite layer 13") in which a part of the zeolite membrane 12 penetrates into the pores. As described above, in FIG. 2, the zeolite membrane 12 and the composite layer 13 are indicated by parallel diagonal lines. In this specification, the composite layer 13 is considered to be a part of the support 11. The composite layer 13 is provided at the interface between the zeolite membrane 12 and the support 11. In a preferred zeolite membrane composite 1, the thickness of the composite layer 13 is smaller than the thickness of the zeolite membrane 12 on the support 11 (i.e., the thickness of the RHO zeolite membrane excluding the composite layer 13).

[0033] Here, the measurement of the thickness of the zeolite membrane 12 and the composite layer 13 will be described. In the measurement of the thickness, first, a cross section perpendicular to the inner circumferential surface of the through hole 111, which is the surface on which the zeolite membrane 12 is formed, is exposed, for example, by cross-sectional polishing. The cross section is photographed using a scanning electron microscope (SEM) to obtain an SEM image. The SEM image shows the periphery of the composite layer 13, as shown in FIG. 2. The magnification of the SEM image is, for example, 5000 times.

[0034] Next, in the vicinity of one measurement position in the direction along the formation surface (interface between the support 11 and the zeolite membrane 12) in the SEM image, the boundary position of the composite layer 13 in the direction perpendicular to the formation surface (hereinafter referred to as the "depth direction") is identified. The boundary position on the zeolite membrane 12 side of the composite layer 13 is the interface between the zeolite membrane 12 and the support 11, and more specifically, the apex of the particle of the support 11 located closest to the zeolite membrane 12 in the depth direction (i.e., the particle located in the outermost layer of the support 11). The boundary position on the opposite side of the composite layer 13 from the zeolite membrane 12 is the edge of the zeolite present in the pores of the support 11 that is farthest from the zeolite membrane 12 in the depth direction (i.e., the inner end of the composite layer 13).

[0035] Then, a distance T3 in the depth direction between a boundary position on the zeolite membrane 12 side of the composite layer 13 and a boundary position on the opposite side of the zeolite membrane 12 is obtained as the thickness of the composite layer 13 at the measurement position. Also, a distance T2 in the depth direction between a surface position of the zeolite membrane 12 away from the support 11 and a boundary position on the zeolite membrane 12 side of the composite layer 13 is obtained as the thickness of the zeolite membrane 12 at the measurement position. In this embodiment, the average value of the thicknesses of the composite layer 13 at a plurality of different measurement positions (for example, 10 measurement positions) is determined as the thickness of the composite layer 13 in the zeolite membrane composite 1. Also, the average value of the thicknesses of the zeolite membrane 12 at a plurality of measurement positions is determined as the thickness of the zeolite membrane 12 in the zeolite membrane composite 1.

[0036] The thickness of the zeolite membrane 12 is, for example, 0.05 μm to 30 μm. The thickness of the zeolite membrane 12 is preferably 5 μm or less, more preferably 4 μm or less, and further preferably 3 μm or less. When the zeolite membrane 12 is made thinner, the amount of highly permeable substances passing through is further increased. The thickness of the zeolite membrane 12 is preferably 0.1 μm or more, and more preferably 0.5 μm or more. When the zeolite membrane 12 is made thicker, the separation performance is improved.

[0037] As described above, in a preferred zeolite membrane composite 1, the thickness of the composite layer 13 is smaller than the thickness of the zeolite membrane 12 on the support 11. The thickness of the composite layer 13 is more preferably 0.8 times or less, and even more preferably 0.5 times or less, of the thickness of the zeolite membrane 12. The thickness of the composite layer 13 is preferably 1 μm or less, more preferably less than 1 μm, and even more preferably 0.5 μm or less. The small thickness of the composite layer 13 suppresses the inhibition of the permeation of the highly permeable substance in the composite layer 13, and the permeation amount of the highly permeable substance is further increased. The smaller the thickness of the composite layer 13, the more preferable it is, and the lower limit of the thickness is not particularly limited, but is, for example, 0.01 μm. The composite layer 13 may not be present.

[0038] Next, an example of a flow of manufacturing the zeolite membrane composite 1 will be described with reference to FIG. 5. When the zeolite membrane composite 1 is manufactured, first, seed crystals to be used in manufacturing the zeolite membrane 12 are prepared (step S11). For example, RHO type zeolite powder is generated by hydrothermal synthesis, and the seed crystals are obtained from the zeolite powder. The RHO type zeolite powder may be generated by any or known manufacturing method (for example, the method of the above-mentioned document 1 or document 2). The zeolite powder may be used as it is as the seed crystals, or the seed crystals may be obtained by processing the powder by pulverization or the like. In the examples described later, the seed crystals can be generated in a short time by mixing the RHO type zeolite powder (seed crystals) with the raw material solution used to generate the seed crystals, but the raw material solution used to generate the seed crystals does not need to contain the powder.

[0039] In addition, as the RHO type zeolite used for the seed crystals, an RHO type zeolite containing SDA may be used, or an RHO type zeolite not containing SDA may be used. An RHO type zeolite not containing SDA can be obtained by synthesizing without using SDA, synthesizing using SDA and then calcining, or the like. Even if the seed crystals are not completely dissolved and remain during membrane formation, a decrease in permeability is unlikely to occur, so it is preferable to use an RHO type zeolite not using SDA as the seed crystals.

[0040] The seed crystals may be crushed as necessary. In order to prevent the crystallinity of the seed crystals from decreasing due to crushing, and the crystallinity of the membrane from decreasing accordingly, it is preferable that the peak intensity at about 2θ=8.3° derived from the (110) plane of the RHO-type zeolite does not decrease by 95% or more due to crushing (i.e., the peak intensity after crushing is more than 5% of the peak intensity before crushing).

[0041] Next, the porous support 11 is immersed in the dispersion liquid in which the seed crystals are dispersed, and the seed crystals are attached to the support 11 (step S12). Alternatively, the dispersion liquid in which the seed crystals are dispersed is brought into contact with a portion of the support 11 on which the zeolite membrane 12 is to be formed, thereby attaching the seed crystals to the support 11. In this way, a seed crystal-attached support is produced. The seed crystals may be attached to the support 11 by other methods.

[0042] The support 11 to which the seed crystals are attached is immersed in the raw material solution. The raw material solution is prepared by dissolving or dispersing, for example, a silicon source, an aluminum source, an alkali source (such as a sodium source or a cesium source), etc. in water as a solvent. The silicon source is, for example, colloidal silica, water glass, fumed silica, etc. The aluminum source is, for example, aluminum hydroxide, sodium aluminate, aluminum sulfate, etc. The sodium source is, for example, sodium hydroxide, sodium chloride, sodium bromide, etc. The cesium source is, for example, cesium hydroxide, cesium chloride, etc.

[0043] In the raw material solution, the molar ratio of silicon / aluminum is 2 to 20, preferably 3 to 15, and more preferably 4 to 10. The molar ratio of sodium / aluminum is 10 to 100, preferably 20 to 90, and more preferably 30 to 80. The molar ratio of cesium / aluminum is 0.5 to 10, preferably 0.7 to 5.0, and more preferably 1.0 to 2.0. The molar ratio of water / aluminum is 500 to 5000, preferably 1000 to 4000, and more preferably 1500 to 3000. The viscosity of the raw material solution at 20°C is, for example, 1 to 150 mPa·s, preferably 2 to 100 mPa·s, and more preferably 3 to 50 mPa·s. The viscosity of the raw material solution can be measured, for example, using an ultrasonic benchtop viscometer (FCV-100H manufactured by Fuji Industrial Co., Ltd.). The raw material solution preferably does not contain SDA, but may contain SDA. The raw material solution may be mixed with other raw materials, and a solvent other than water may be used for the raw material solution.

[0044] After the support 11 is immersed in the raw material solution, the RHO-type zeolite is grown by hydrothermal synthesis using the seed crystals on the support 11 as nuclei, and the RHO-type zeolite membrane 12 is formed on the support 11 (step S13). The temperature during the hydrothermal synthesis is preferably 60 to 200°C. The hydrothermal synthesis time is preferably 1 to 20 hours. The shorter the hydrothermal synthesis time, the more the production cost of the zeolite membrane composite 1 can be reduced. When the hydrothermal synthesis is completed, the support 11 and the zeolite membrane 12 are washed with pure water. The support 11 and the zeolite membrane 12 after washing are dried at, for example, 50°C. Through the above treatment, a dense zeolite membrane 12 is formed, and the above-mentioned zeolite membrane composite 1 having high separation performance and permeation amount is produced. When the raw material solution contains SDA, the zeolite membrane 12 is heat-treated under an oxidizing gas atmosphere to burn and remove the SDA in the zeolite membrane 12. Preferably, the SDA is almost completely removed.

[0045] The particle size of the zeolite particles constituting the zeolite membrane 12 is, for example, 0.01 μm to 1 μm, preferably 0.05 to 0.9 μm, and more preferably 0.1 to 0.8 μm. The particle size of the zeolite particles is determined by observing the surface of the zeolite membrane 12 with a scanning electron microscope (SEM) and arithmetically averaging the particle sizes of any 20 zeolite particles.

[0046] The zeolite membrane 12 may be ion-exchanged as necessary. When a Cs source is used to synthesize the RHO-type zeolite membrane, the presence of Cs ions in the pores is expected to improve the separation coefficient, but may decrease the permeability coefficient. Ions to be exchanged include protons, ammonium ions, Na + , K + , Li + Alkali metal ions such as Ca 2+ , Mg 2+ , Sr 2+ , B.A. 2+ Alkaline earth metal ions such as Fe 2+ , Fe 3+ , Cu 2+ , Zn 2+ , Ag + and the like transition metal ions.

[0047] Next, separation of a mixed substance using the zeolite membrane composite 1 will be described with reference to Fig. 6 and Fig. 7. Fig. 6 is a diagram showing a separation device 2. Fig. 7 is a diagram showing a flow of separation of a mixed substance by the separation device 2.

[0048] In the separation device 2, a mixed substance containing a plurality of types of fluids (i.e., gas or liquid) is supplied to the zeolite membrane composite 1, and a substance having high permeability in the mixed substance (i.e., a highly permeable substance) is separated from the mixed substance by permeating the zeolite membrane composite 1. The separation in the separation device 2 may be performed, for example, for the purpose of extracting a highly permeable substance from the mixed substance, or for the purpose of concentrating a substance having low permeability (hereinafter also referred to as a "low permeable substance").

[0049] The mixed substance (i.e., mixed fluid) may be a mixed gas containing multiple types of gases, a mixed liquid containing multiple types of liquids, or a gas-liquid two-phase fluid containing both gas and liquid.

[0050] The mixture includes, for example, one or more of hydrogen (H2), helium (He), nitrogen (N2), oxygen (O2), water (H2O), water vapor (H2O), carbon monoxide (CO), carbon dioxide (CO2), nitrogen oxides, ammonia (NH3), sulfur oxides, hydrogen sulfide (H2S), sulfur fluoride, mercury (Hg), arsine (AsH3), hydrogen cyanide (HCN), carbonyl sulfide (COS), C1-C8 hydrocarbons, organic acids, alcohols, mercaptans, esters, ethers, ketones, and aldehydes. The highly permeable substance is, for example, one or more of H2, He, N2, O2, CO2, NH3, and H2O, and is preferably H2O.

[0051] Nitrogen oxides are compounds of nitrogen and oxygen. Examples of the above-mentioned nitrogen oxides include nitric oxide (NO), nitrogen dioxide (NO2), nitrous oxide (also called dinitrogen monoxide) (N2O), dinitrogen trioxide (N2O3), dinitrogen tetroxide (N2O4), dinitrogen pentoxide (N2O5), etc. X The gas is called NOX.

[0052] Sulfur oxides are compounds of sulfur and oxygen. The above-mentioned sulfur oxides include, for example, sulfur dioxide (SO2), sulfur trioxide (SO3), and other SO X The gas is called SOXX.

[0053] Sulfur fluoride is a compound of fluorine and sulfur. The above-mentioned sulfur fluoride is, for example, disulfur difluoride (FSSF, S = SF2), sulfur difluoride (SF2), sulfur tetrafluoride (SF4), sulfur hexafluoride (SF6) or disulfur decafluoride (S2F 10 ) etc.

[0054] C1-C8 hydrocarbons are those with 1 to 8 carbon atoms. C3-C8 hydrocarbons may be straight-chain compounds, side-chain compounds, or cyclic compounds. C2-C8 hydrocarbons may be saturated hydrocarbons (i.e., those with no double or triple bonds in the molecule) or unsaturated hydrocarbons (i.e., those with double or triple bonds in the molecule). C1-C4 hydrocarbons are, for example, methane (CH4), ethane (C2H6), ethylene (C2H4), propane (C3H8), propylene (C3H6), normal butane (CH3(CH2)2CH3), isobutane (CH(CH3)3), 1-butene (CH2=CHCH2CH3), 2-butene (CH3CH=CHCH3), or isobutene (CH2=C(CH3)2).

[0055] The organic acid may be a carboxylic acid or a sulfonic acid. The carboxylic acid may be, for example, formic acid (CH2O2), acetic acid (C2H4O2), oxalic acid (C2H2O4), acrylic acid (C3H4O2), or benzoic acid (C6H5COOH). The sulfonic acid may be, for example, ethanesulfonic acid (C2H6O3S). The organic acid may be a chain compound or a cyclic compound.

[0056] The above-mentioned alcohols are, for example, methanol (CH3OH), ethanol (C2H5OH), isopropanol (2-propanol) (CH3CH(OH)CH3), ethylene glycol (CH2(OH)CH2(OH)) or butanol (C4H9OH).

[0057] Mercaptans are organic compounds that have hydrogenated sulfur (SH) at the end, and are also called thiols or thioalcohols. Examples of the mercaptans mentioned above include methyl mercaptan (CH3SH), ethyl mercaptan (C2H5SH), and 1-propanethiol (C3H7SH).

[0058] The esters mentioned above are, for example, formates or acetates.

[0059] The above-mentioned ethers are, for example, dimethyl ether ((CH3)2O), methyl ethyl ether (C2H5OCH3) or diethyl ether ((C2H5)2O).

[0060] The above-mentioned ketones are, for example, acetone ((CH3)2CO), methyl ethyl ketone (C2H5COCH3) or diethyl ketone ((C2H5)2CO).

[0061] The above-mentioned aldehydes are, for example, acetaldehyde (CH3CHO), propionaldehyde (C2H5CHO) or butanal (butyraldehyde) (C3H7CHO).

[0062] In the following description, the mixed substance separated by the separation device 2 will be described as a mixed liquid containing a plurality of types of liquid.

[0063] The separation device 2 includes a zeolite membrane composite 1, a plugging section 21, an outer cylinder 22, two seal members 23, a supply section 26, a first recovery section 27, and a second recovery section 28. The zeolite membrane composite 1, the plugging section 21, and the seal members 23 are housed in the outer cylinder 22. The supply section 26, the first recovery section 27, and the second recovery section 28 are disposed outside the outer cylinder 22 and connected to the outer cylinder 22.

[0064] The sealing portion 21 is a member attached to both ends of the support 11 in the longitudinal direction (i.e., the left-right direction in FIG. 6) and covers and seals both longitudinal end faces of the support 11 and the outer peripheral surfaces near the both end faces. The sealing portion 21 prevents the inflow and outflow of liquid from the both end faces of the support 11. The sealing portion 21 is, for example, a plate-like member formed of glass or resin. The material and shape of the sealing portion 21 may be changed as appropriate. Note that the sealing portion 21 has a plurality of openings that overlap with the plurality of through holes 111 of the support 11, and therefore both longitudinal ends of each through hole 111 of the support 11 are not covered by the sealing portion 21. Therefore, liquid and the like can flow into and out of the through holes 111 from both ends.

[0065] The shape of the outer cylinder 22 is not particularly limited, and is, for example, a substantially cylindrical tubular member. The outer cylinder 22 is formed of, for example, stainless steel or carbon steel. The longitudinal direction of the outer cylinder 22 is substantially parallel to the longitudinal direction of the zeolite membrane composite 1. A supply port 221 is provided at one end of the outer cylinder 22 in the longitudinal direction (i.e., the end on the left side in FIG. 6), and a first discharge port 222 is provided at the other end. A second discharge port 223 is provided on the side surface of the outer cylinder 22. A supply unit 26 is connected to the supply port 221. A first recovery unit 27 is connected to the first discharge port 222. A second recovery unit 28 is connected to the second discharge port 223. The internal space of the outer cylinder 22 is a sealed space isolated from the space around the outer cylinder 22.

[0066] The two seal members 23 are disposed around the entire circumference between the outer circumferential surface of the zeolite membrane composite 1 and the inner circumferential surface of the outer tube 22 near both longitudinal ends of the zeolite membrane composite 1. Each seal member 23 is a substantially annular member made of a material that is impermeable to liquid. The seal member 23 is, for example, an O-ring made of a flexible resin. The seal member 23 is in close contact with the outer circumferential surface of the zeolite membrane composite 1 and the inner circumferential surface of the outer tube 22 around the entire circumference. In the example shown in FIG. 6, the seal member 23 is in close contact with the outer circumferential surface of the sealing portion 21 and indirectly in close contact with the outer circumferential surface of the zeolite membrane composite 1 via the sealing portion 21. The seal member 23 and the outer circumferential surface of the zeolite membrane composite 1 and the seal member 23 and the inner circumferential surface of the outer tube 22 are sealed, and liquid is hardly or completely prevented from passing through them.

[0067] The supply unit 26 supplies the mixed liquid to the internal space of the outer cylinder 22 through the supply port 221. The supply unit 26 includes, for example, a pump that pressure-feeds the mixed liquid toward the outer cylinder 22. The pump includes a temperature control unit and a pressure control unit that respectively control the temperature and pressure of the mixed liquid supplied to the outer cylinder 22. The first recovery unit 27 includes, for example, a storage container that stores the liquid drawn out from the outer cylinder 22, or a pump that transfers the liquid. The second recovery unit 28 includes, for example, a vacuum pump that reduces the pressure of the space outside the outer circumferential surface of the zeolite membrane composite 1 in the outer cylinder 22 (i.e., the space sandwiched between the two seal members 23), and a liquid nitrogen trap that cools and liquefies the gas that has permeated the zeolite membrane composite 1 while vaporizing.

[0068] When the mixed liquid is separated, the above-mentioned separation device 2 is prepared to prepare the zeolite membrane composite 1 (FIG. 7: step S21). Then, the mixed liquid containing a plurality of types of liquids having different permeabilities to the zeolite membrane 12 is supplied to the internal space of the outer cylinder 22 by the supply unit 26. For example, the main components of the mixed liquid are water (H2O) and ethanol (C2H5OH). The mixed liquid may contain liquids other than water and ethanol. The pressure of the mixed liquid supplied from the supply unit 26 to the internal space of the outer cylinder 22 (i.e., the introduction pressure) is, for example, 0.1 MPa to 2 MPa, and the temperature of the mixed liquid is, for example, 10°C to 200°C.

[0069] The mixed liquid supplied from the supply unit 26 to the outer cylinder 22 is introduced into each through-hole 111 of the support 11 from the left end of the zeolite membrane composite 1 in the figure, as indicated by an arrow 251. A highly permeable substance, which is a liquid with high permeability in the mixed liquid, vaporizes and permeates through the zeolite membrane 12 provided on the inner circumferential surface of each through-hole 111 and the support 11, and is discharged from the outer circumferential surface of the support 11. As a result, the highly permeable substance (e.g., water) is separated from a low-permeable substance (e.g., ethanol), which is a liquid with low permeability in the mixed liquid (step S22).

[0070] The gas (hereinafter referred to as the "permeating substance") discharged from the outer peripheral surface of the support 11 is led to the second recovery section 28 via the second discharge port 223 as shown by the arrow 253, where it is cooled and recovered as a liquid. The pressure of the gas recovered by the second recovery section 28 via the second discharge port 223 (i.e., the permeation pressure) is, for example, about 50 Torr (about 6.67 kPa). The permeating substance may include a low permeable substance that has permeated the zeolite membrane 12 in addition to the above-mentioned high permeable substances.

[0071] In addition, the liquid other than the substance that has permeated the zeolite membrane 12 and the support 11 (hereinafter referred to as "non-permeating substance") in the mixed liquid passes through each through-hole 111 of the support 11 from the left side to the right side in the figure, and is recovered by the first recovery section 27 through the first discharge port 222 as shown by the arrow 252. The pressure of the liquid recovered by the first recovery section 27 through the first discharge port 222 is, for example, approximately the same as the introduction pressure. The non-permeating substance may include a highly permeable substance that has not permeated the zeolite membrane 12, in addition to the above-mentioned low-permeability substance. The non-permeating substance recovered by the first recovery section 27 may be circulated to the supply section 26, for example, and supplied again into the outer casing 22.

[0072] Next, examples of zeolite membrane composites will be described. Table 1 shows the compositions (compositions calculated as oxides) of raw material solutions for forming zeolite membranes and the conditions of hydrothermal synthesis prepared in Examples 1 to 7 and Comparative Examples 1 and 2.

[0073] [Table 1]

[0074] Example 1 Colloidal silica (Nissan Chemical's Snowtex S), aluminum hydroxide (Sigma-Aldrich), sodium hydroxide (Sigma-Aldrich), 50% aqueous cesium hydroxide solution, and ion-exchanged water were mixed in a molar ratio of 10.8SiO2:1Al2O3:3Na2O:0.4Cs2O:110H2O in 100g portions, and mixed overnight (12 hours or more) in a shaker. 0.1g of RHO-type zeolite powder (seed crystals for seed crystal generation) was added to the gel obtained. The gel was heated at 100°C for 30 hours to perform hydrothermal synthesis, and seed crystals were obtained. The seed crystals obtained above were then applied to a tubular zirconia porous support having a diameter of 10 mm and a length of 160 mm.

[0075] Next, 200 g of colloidal silica (Nissan Chemical's Snowtex S), aluminum hydroxide (Sigma-Aldrich), sodium hydroxide (Sigma-Aldrich), 50% aqueous cesium hydroxide solution, and ion-exchanged water were mixed together in a molar ratio of 10SiO2:1Al2O3:40Na2O:10Cs2O:2000H2O as a raw material solution (synthetic sol) for forming a zeolite membrane, and mixed overnight with a shaker. The viscosity of the raw material solution at 20°C was measured using an ultrasonic tabletop viscometer (Fuji Kogyo Co., Ltd. FCV-100H), and was found to be 10 mPa·s. The zirconia support coated with seed crystals and the obtained raw material solution were placed in a Teflon (registered trademark) container and heated at 100°C for 10 hours to perform hydrothermal synthesis, forming an RHO-type zeolite membrane on the support. Thereafter, the support and the zeolite membrane were washed with water and dried overnight at 50° C. in a dryer to obtain a zeolite membrane composite.

[0076] Example 2 The composition of the raw material solution was changed to 10SiO2:1Al2O3:100Na2O:10Cs2O:2000H2O, but the procedure was the same as in Example 1. The viscosity of the raw material solution (20°C) was 5 mPa·s.

[0077] Example 3 The composition of the raw material solution was changed to 10SiO2:1Al2O3:10Na2O:10Cs2O:2000H2O, but the procedure was the same as in Example 1. The viscosity of the raw material solution (20°C) was 20 mPa·s.

[0078] Example 4 The composition of the raw material solution was changed to 20SiO2:1Al2O3:40Na2O:10Cs2O:2000H2O, but the procedure was the same as in Example 1. The viscosity of the raw material solution (20°C) was 12 mPa·s.

[0079] Example 5 The composition of the raw material solution was changed to 10SiO2:1Al2O3:40Na2O:10Cs2O:5000H2O, but the procedure was the same as in Example 1. The viscosity of the raw material solution (20°C) was 7 mPa·s.

[0080] Example 6 The composition of the raw material solution was changed to 20SiO2:1Al2O3:10Na2O:1Cs2O:1000H2O, and the synthesis temperature in the hydrothermal synthesis was changed to 110° C. The procedure was the same as in Example 1. The viscosity of the raw material solution (20° C.) was 30 mPa s.

[0081] Example 7 Except for changing the support to a monolithic alumina porous support having a diameter of 30 mm and a length of 160 mm, the procedure was the same as in Example 1. The viscosity of the raw material solution (20° C.) was 10 mPa·s.

[0082] Comparative Example 1 The support was the same zirconia support as in Example 1, and the seed crystals were applied in the same manner as in Example 1. The composition of the raw solution was 10.8SiO2:1Al2O3:3Na2O:0.4Cs2O:110H2O, and the solution was heated at 110°C for 144 hours for hydrothermal synthesis to obtain an RHO-type zeolite membrane. The viscosity of the raw solution (20°C) was 1200 mPa s.

[0083] Comparative Example 2 A zeolite membrane was formed in the same manner as in Comparative Example 1, except that the hydrothermal synthesis conditions were changed to 110° C. for 24 hours.

[0084] (Measurement and evaluation of zeolite membrane composites) Various measurements were performed on the zeolite membrane composites of Examples 1 to 7 and Comparative Examples 1 and 2. First, the surface of the zeolite membrane was measured by X-ray diffraction (XRD measurement). In the XRD measurement, an X-ray diffractometer (device name: MiniFlex600) manufactured by Rigaku Corporation was used. The XRD measurement was performed at a tube voltage of 40 kV, a tube current of 15 mA, a scanning speed of 0.5° / min, and a scanning step of 0.02°. The divergence slit was 1.25°, the scattering slit was 1.25°, the receiving slit was 0.3 mm, the incident Soller slit was 5.0°, and the receiving Soller slit was 5.0°. No monochromator was used, and a 0.015 mm thick nickel foil was used as a CuKβ ray filter. In the zeolite membrane composites of Examples 1 to 7, the peak intensity in the vicinity of 2θ=18.7° in the XRD pattern was 0.4 times or less than the peak intensity in the vicinity of 2θ=8.3°, and the peak intensity in the vicinity of 2θ=14.4° was 0.3 times or less than the peak intensity in the vicinity of 2θ=8.3°. In other words, the peak intensity derived from the (310) plane of RHO-type zeolite was 0.4 times or less than the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane was 0.3 times or less than the peak intensity derived from the (110) plane. Note that FIG. 3 described above is an XRD pattern obtained from the zeolite membrane composite of Example 1.

[0085] In contrast, in the zeolite membrane composites of Comparative Examples 1 and 2, the peak intensity in the XRD patterns around 2θ=18.7° was more than 0.4 times the peak intensity in the vicinity of 2θ=8.3°, and the peak intensity in the vicinity of 2θ=14.4° was more than 0.3 times the peak intensity in the vicinity of 2θ=8.3°. That is, the peak intensity derived from the (310) plane of RHO-type zeolite was more than 0.4 times the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane was more than 0.3 times the peak intensity derived from the (110) plane.

[0086] The silicon / aluminum molar ratio (Si / Al ratio) of the zeolite membrane was measured by EDS analysis. In the EDS analysis, the acceleration voltage was set to 10 kV or less. As shown in Table 2, the silicon / aluminum molar ratio was in the range of 1 to 10 in the zeolite membrane composites of Examples 1 to 7 and Comparative Examples 1 and 2.

[0087] [Table 2]

[0088] Further, the thickness of the zeolite membrane and the composite layer was measured for each zeolite membrane composite. In the thickness measurement, as described with reference to FIG. 2, a cross section of the zeolite membrane composite perpendicular to the formation surface of the zeolite membrane on the support was exposed, and an SEM image of the cross section was obtained using a scanning electron microscope (SEM). The magnification of the SEM image was 5000 times. Next, in the SEM image, the boundary positions on both sides of the composite layer in the depth direction were identified near one measurement position in the direction along the formation surface. Then, the distance in the depth direction between the boundary position on the zeolite membrane side of the composite layer and the boundary position on the opposite side to the zeolite membrane was obtained as the thickness of the composite layer at the measurement position. Also, the distance in the depth direction between the position of the surface of the zeolite membrane and the boundary position on the zeolite membrane side of the composite layer was obtained as the thickness of the zeolite membrane at the measurement position.

[0089] For each zeolite membrane composite, the average thickness of the composite layer at 10 different measurement positions was calculated and determined as the thickness of the composite layer in the zeolite membrane composite. Similarly, the average thickness of the zeolite membrane at 10 measurement positions was calculated and determined as the thickness of the zeolite membrane in the zeolite membrane composite. Table 2 also shows the thickness of the zeolite membrane and the thickness of the composite layer.

[0090] In Examples 1 to 7, the thickness of the composite layer was smaller than the thickness of the zeolite membrane, whereas in Comparative Examples 1 and 2, the thickness of the composite layer was larger than the thickness of the zeolite membrane. In addition, the thickness of the zeolite membrane in each of the zeolite membrane composites was 5 μm or less. Meanwhile, the thickness of the composite layer was less than 1 μm in Examples 1 to 7, whereas it was significantly larger than 1 μm in Comparative Examples 1 and 2.

[0091] In the evaluation of the zeolite membrane composite, the separation factor and the water permeation amount were measured. The separation factor and the water permeation amount were obtained from the permeating material (i.e., the permeated liquid) that permeated the zeolite membrane composite 1 and was recovered in the second recovery section 28 by supplying a mixed liquid of water and ethanol from the supply section 26 to the zeolite membrane composite 1 in the outer cylinder 22 in the above-mentioned separation device 2. Specifically, the separation factor was a value obtained by dividing the water concentration (mass%) in the permeating material recovered in the second recovery section 28 by the ethanol concentration (mass%) in the permeating material recovered in the second recovery section 28 (i.e., the separation ratio between water and ethanol). The water permeation amount was obtained from the amount of water in the permeating material recovered in the second recovery section 28. The temperature of the mixed liquid supplied from the supply section 26 was 60°C, the proportions of water and ethanol in the mixed liquid were each 50 mass%, and the permeation pressure (permeation side vacuum degree) was 50 Torr.

[0092] As shown in Table 2, the zeolite membrane composites of Comparative Examples 1 and 2 had separation factors of 800 or less. In contrast, the zeolite membrane composites of Examples 1 to 7 all had separation factors of more than 1500, and highly dense RHO-type zeolite membranes were obtained. In addition, in Examples 1 to 7, the water permeation amount (water flux) was 1.3 kg / m 2 h or more, and a high water permeation rate was also obtained.

[0093] As described above, the raw solutions of Examples 1 to 7 have sufficiently low viscosity and high fluidity compared to the raw solutions of Comparative Examples 1 and 2. It is believed that this makes it possible to form a dense zeolite membrane. In addition, the zeolite membrane composites of Examples 1 to 7 have a smaller composite layer thickness compared to the zeolite membrane composites of Comparative Examples 1 and 2. This is because the raw solutions of Examples 1 to 7 act preferentially on the seed crystals, that is, it is believed that zeolite is not easily generated in the parts of the support where there are no seed crystals (for example, in the pores). On the other hand, the raw solutions of Comparative Examples 1 and 2 have a high concentration, and zeolite is easily generated even in the pores of the support where there are no seed crystals. In Comparative Example 2, the separation coefficient is extremely low, so a rough zeolite membrane with many gaps is formed, and the water permeation amount is relatively high. In Comparative Example 1, the composite membrane is thick, so the water permeation amount is low.

[0094] As described above, the zeolite membrane composite 1 includes the porous support 11 and the zeolite membrane 12 formed on the support 11 and made of RHO-type zeolite. When the surface of the zeolite membrane 12 is measured by X-ray diffraction, the peak intensity derived from the (310) plane of the RHO-type zeolite is 0.4 times or less than the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane is 0.3 times or less than the peak intensity derived from the (110) plane. Thus, in the zeolite membrane composite 1, the zeolite membrane 12 is an oriented membrane with a high peak intensity derived from the (110) plane, and many pore openings are located on the surface of the zeolite membrane 12. As a result, a zeolite membrane composite 1 having high separation performance and high permeation amount can be easily provided.

[0095] In a preferred zeolite membrane composite 1, a composite layer 13 is provided on a support 11 in which a part of the zeolite membrane 12 penetrates into the pores, and the thickness of the composite layer 13 is smaller than the thickness of the zeolite membrane 12 on the support 11. This prevents the permeation of highly permeable substances from being hindered by the composite layer 13, and the permeation amount of the highly permeable substances can be further increased. More preferably, the thickness of the zeolite membrane 12 is 5 μm or less, and the thickness of the composite layer 13 is 1 μm or less. In such a zeolite membrane composite 1, the permeation amount of the highly permeable substances can be further increased.

[0096] Preferably, the silicon / aluminum molar ratio in the zeolite membrane 12 is 1 to 10. This can improve the hydrophilicity of the zeolite membrane 12, and in the case where water is a highly permeable substance, can further increase the separation performance and permeation amount of the zeolite membrane composite 1. In other words, the zeolite membrane 12 can be suitably used as a dehydration membrane.

[0097] The method for producing the zeolite membrane composite 1 includes a step of attaching seed crystals of RHO type zeolite onto a porous support 11, and a step of immersing the support 11 in a raw material solution and growing RHO type zeolite from the seed crystals by hydrothermal synthesis to form a zeolite membrane 12 on the support 11. In addition, in the raw material solution, the molar ratio of silicon / aluminum is 2 to 20, the molar ratio of sodium / aluminum is 10 to 100, the molar ratio of cesium / aluminum is 0.5 to 10, and the molar ratio of water / aluminum is 500 to 5000. This makes it possible to easily provide a zeolite membrane composite 1 having high separation performance and permeation amount.

[0098] Furthermore, when the viscosity of the raw material solution at 20° C. is in the range of 1 to 150 mPa·s, the zeolite membrane composite 1 having high separation performance and high permeation amount can be produced more reliably.

[0099] In order to improve the density of the zeolite membrane, it is conceivable to repeat the hydrothermal synthesis multiple times, but in this case, the thicknesses of the zeolite membrane and the composite layer increase, resulting in a low permeation amount. In contrast, in the method for producing the zeolite membrane composite 1, by adjusting the raw material solution as described above, it becomes possible to form a dense zeolite membrane 12 while reducing the thicknesses of the zeolite membrane 12 and the composite layer 13.

[0100] The above-mentioned zeolite membrane composite 1 and the method for producing the zeolite membrane composite 1 can be modified in various ways.

[0101] In the zeolite membrane composite 1, when a certain degree of permeation amount is ensured, the thickness of the composite layer 13 may be equal to or greater than the thickness of the zeolite membrane 12 on the support 11. In addition, the thickness of the zeolite membrane 12 may be greater than 5 μm, and the thickness of the composite layer 13 may be greater than 1 μm.

[0102] The silicon / aluminum molar ratio in the zeolite membrane 12 may be greater than ten.

[0103] In the support 11 having through-holes, the zeolite membrane 12 may be provided on either the inner peripheral surface or the outer peripheral surface, or on both the inner peripheral surface and the outer peripheral surface.

[0104] As long as the zeolite membrane composite 1 can be appropriately produced, the viscosity at 20° C. of the raw material solution used for forming the zeolite membrane 12 may be outside the range of 1 to 150 mPa s. In addition, the zeolite membrane composite 1 may be produced by a method other than the above-mentioned production method.

[0105] The zeolite membrane composite 1 may further include a functional membrane or a protective membrane laminated on the zeolite membrane 12, in addition to the support 11 and the zeolite membrane 12. Such a functional membrane or protective membrane may be an inorganic membrane such as a zeolite membrane, a silica membrane, or a carbon membrane, or an organic membrane such as a polyimide membrane or a silicone membrane. In addition, a substance that easily adsorbs water may be added to the functional membrane or protective membrane laminated on the zeolite membrane 12.

[0106] In the separation device 2 and the separation method, the mixture may be separated by a vapor permeation method, a reverse osmosis method, a gas permeation method, or the like, in addition to the pervaporation method exemplified in the above description.

[0107] In the separation device 2 and the separation method, substances other than the substances exemplified in the above description may be separated from the mixed substance.

[0108] The configurations in the above-described embodiment and each of the modified examples may be combined as appropriate as long as they are not mutually inconsistent.

[0109] Although the invention has been particularly illustrated and described, it is to be understood that the above description is illustrative and not restrictive, and therefore numerous modifications and variations are possible without departing from the scope of the invention. [Industrial Applicability]

[0110] The zeolite membrane composite of the present invention can be used, for example, as a dehydration membrane, and further, can be used in various fields in which zeolites are used, such as separation membranes for various substances other than water and adsorption membranes for various substances. [Explanation of symbols]

[0111] 1 Zeolite membrane composite 11 Support 12 Zeolite membrane 13 Composite layer S11~S13, S21, S22 steps

Claims

1. A zeolite membrane composite, A porous support; a zeolite membrane formed on the support and made of RHO-type zeolite; Equipped with When the surface of the zeolite membrane is measured by an X-ray diffraction method, the peak intensity derived from the (310) plane of the RHO zeolite is 0.4 times or less of the peak intensity derived from the (110) plane, and the peak intensity derived from the (211) plane is 0.3 times or less of the peak intensity derived from the (110) plane, The zeolite membrane composite has a silicon / aluminum molar ratio of 1.2 to 3.

0.

2. The zeolite membrane composite according to claim 1, A composite layer is provided on the support, with a part of the zeolite membrane penetrating into pores, and the thickness of the composite layer is smaller than the thickness of the zeolite membrane on the support.

3. The zeolite membrane composite according to claim 2, The thickness of the zeolite membrane is 5 μm or less, The zeolite membrane composite, wherein the composite layer has a thickness of 1 μm or less.

4. A method for producing a zeolite membrane composite, comprising the steps of: a) attaching seed crystals of RHO zeolite onto a porous support; b) immersing the support in a raw material solution and growing RHO-type zeolite from the seed crystals by hydrothermal synthesis to form a zeolite membrane on the support; Equipped with In the raw material solution, the molar ratio of silicon / aluminum is 2 to 20, the molar ratio of sodium / aluminum is 10 to 100, the molar ratio of cesium / aluminum is 0.5 to 10, the molar ratio of water / aluminum is 500 to 5000, and the molar ratio of H 2 O / SiO 2 is 50 to 500.

5. A method for producing the zeolite membrane composite according to claim 4, comprising the steps of: The viscosity of the raw material solution at 20° C. is 1 to 150 mPa·s.

Citation Information

Patent Citations

  • Porous support-zeolite membrane composite body, method for producing RHO type zeolite and separation method

    JP2018130719A

  • RHO type zeolite and manufacturing method therefor

    JP2020066564A

  • Ammonia separation method and zeolite

    WO2018230737A1